Integrated logistics and economic reforms in Ukraine - Ковалевский, Георгий Валентинович (Eastern-European Journal of Enterprise Technologies, 2012)
The new ideas, approaches and solutions in the economy and management are developed. The analysis of the new economy of E.G. Lieberman is given. The new ideas, approaches and concepts such as "integrated economy", the phenomenon of the time factor," "integrated system", "integrated management" to address critical economic and social problems are introduced for the first time